Kansas Land Prices and Cash Rental Rates - Dhuyvetter, Kevin C.; Kastens, Terry L. (My University, 2006)
This farm management guide reports Kansas land prices and cash rental rates for 1987-2006. The data is meant to be useful to farm managers.
MF1100_2006_10
Keywords: MF1100; Economics; MF